Uncoolness factor of collaborative Web Mining Tools (WMT) - Chulilla, Juan Luis; Azagra, Pilar (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
The recent development of social mining is a useful and direct analogy to talking about the less visible part of the adoption of successive waves of social software. The striking fact of visibility decrease as each type of social software matures should be taken into account for any comprehensive analysis of the relation between collectives and Internet technologies. One of the main results of this relation is the social data mining of Internet, which both gives sense to virtual communities and produces contents via feedback. We are just at the beginning of the adoption of new ways of social data mining, which will be significant when grow mature and become invisible.
Keywords: web mining; web 2.0; IJIMAI